Advertising policies and their role in increasing the market share: An applied study on Saleh Hussain Al Salama Group of Companies, Kingdom of Saudi Arabia - Alghamdi, Bandar Abdulraheem (Journal of Economic, Administrative and Legal Sciences, 2024)
The aim of the research is to highlight the role of advertising policies in increasing the market share, in addition to the role played by the tools of attracting the audience and its role in increasing the market share, and the effect of advertising means on increasing the market share, in addition to determining the extent of the institution’s interest in the basic principles of organizing advertising activities in increasing the market share, The study was applied in Saleh Hussain Al Salama Group of Companies in the Kingdom of Saudi Arabia, To achieve the objectives of the research, the researcher used the descriptive analytical approach, where the questionnaire was used as a tool to collect data from the sample of the study,  which was made up of (128) employees of the Group of Companies Saleh Hussein Al Salama, selected in the method of Intentional  sample, The research found several results, the most important of which was a statistically significant relationship between advertising policies and increased market share, a statistically functioning relationship between the basic principles of advertising regulation and increased market share, a statistically significant relationship between target audience attraction tools and increased market share, and finally a statistically functioning relationship between advertising distribution methods and increased market share, The research recommended that the basic principles of organizing advertising activities should be relied upon in timely decision-making, that the basic principles of organizing advertising activities contribute to objective and realistic information.
Keywords: advertising; advertising policies; market share; increased market share